Microwave Assisted Chemical Modification of Graphite Oxide for Supercapacitor Application - Siddharthan, R.; Mahalingam, P.; Kanagaraj, E.; Saravanan, K. (Asian Journal of Chemistry, 2021)
In present work, graphite oxide was chemically modified with boron, nitrogen and sulfur co-doping in a simple, single step green method by microwave treatment. Borax, urea and thiourea were used as precursors for doping. Mixtures of graphite oxide with precursors were microwave treated using domestic microwave oven at 800 W for 5 min. The products obtained were characterized for its morphology, structure, composition and electrical properties. The results showed that simultaneous reduction of graphite oxide and doping of boron, nitrogen and sulfur were occurred. The elemental doping distorts the structure without much affecting the crystalline nature. The boron, nitrogen and sulfur elements were doped in graphite oxide to the extent of 9.97 at%, 2.67 at% and 0.84 at%, respectively. The cyclic voltammetry and electrochemical impedance spectroscopy studies showed that boron, nitrogen and sulfur co-doped graphite oxide could be a suitable material for supercapacitor application.